Pendampingan Petani Gaharu melalui Program Diversifikasi Produk Gaharu sebagai Usaha Peningkatan Pendapatan Petani Gaharu di Kabupaten Bangka Tengah - Henny Helmi; Eni Karsiningsih (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
Agarwood is a kind of fragrant wood which used as raw material in parfume industry, cosmetics, and medicine. Agarwood was formed by infected of fungy to several species from plant of genus Acquillaria. Farmer groups (Gapoktan Alam Jaya Lestari and Poktan Air Pasir Maju) are partners involved in this program. Both of these farmers groups had problems in availability of inoculant and the expensive price of inoculant. Besides, group farmers havenot known well of inoculatuion techniques. This program was conducted by Participation Action Researh (PAR). Fungi inoculant propagation were practiced in a simple way using potato and sugar as raw materials. Both of partners were very passionate on inoculant training activities, even farmers wanted to try to make inoculants of various materials which avalaible at their sourrounding. On the inoculation techniques, spiral method using both liquid and powders inoculants were injected to gaharu plant. Farmers were trained drafting technique as alternative product of agarwood such as tasbeeh. In addition, farmers trained to calculate a profit of agarwood product. To be independent farmer group, Poktan Air Pasir Maju still needs to be trained further because of their strong willingness to develop agarwood but still lacking skill.